Screening Techniques for Different Insect Pests in Crop Plants - Kavitha, K.; Reddy, K. Dharma (International Journal of Bio-resource and Stress Management, 2012)
Insect resistance in crop plants is an important component of Integrated Pest Management (IPM) and it is considered as non-monetary input at farmers end. Resistant and tolerant cultivars form the basic component of Integrated Pest Management (IPM) over which other components are to be built up. Even a low level of tolerance in plants has a dramatic effect, which in fact reduces the need of insecticides. Use of resistant or less-susceptible cultivars is one of the most important methods of keeping insect populations below economic threshold levels. However, host-plant resistance is not a panacea for all pest problems. It is most useful when carefully utilized with other components of pest management. Screening techniques vary with crop and pest. Thorough knowledge regarding the pest life cycle and screening techniques enable breeder to breed for pest resistant varieties thus combating biotic stresses and reaping good yield which is the need of the hour